233k views
4 votes
Check if the following equality is true for all values of variables: (a–3c)(4c+2a)+3c(a+3c)=(2a–c)(3c+5a)–8a^2

1 Answer

0 votes

Answer:

True for all values of a, b and c.

Explanation:

(a–3c)(4c+2a)+3c(a+3c)=(2a–c)(3c+5a)–8a^2

Left side:

(a–3c)(4c+2a)+3c(a+3c)

= 4ac + 2a^2 - 12c^2 - 6ac + 3ac + 9c^2

= 2a^2 + ac - 3c^2

Right side:

(2a–c)(3c+5a)–8a^2

= 6ac + 10a^2 - 3c^2 - 5ac - 8a^2

= 2a^2 + ac - 3c^2.

So we see that the left side is identical to the right side so it is true for all values of the variables.

User Azatoth
by
6.5k points